2013
DOI: 10.1002/ejoc.201201660
|View full text |Cite
|
Sign up to set email alerts
|

Off the Beaten Track: The Use of Secondary Amines in the Ugi Reaction

Abstract: Although the Ugi multicomponent reaction is more than 40 years old, there is still room for its application to the discovery of new multicomponent transformations, even within the constraints of its classic four‐reactant menu (aldehyde, amine, carboxylic acid, and isocyanide). Replacement of a primary amine with a secondary one thus allows the Mumm‐like rearrangement step to be avoided, freezing the reaction course at the stage of an imino‐anhydride intermediate susceptible to alternative nucleophilic trapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 47 publications
0
29
1
Order By: Relevance
“…1 Reactions of isocyanides with secondary amines and aldehydes/ketones represent a special case, as the prototypical Mumm rearrangement cannot take place. 2 …”
mentioning
confidence: 99%
“…1 Reactions of isocyanides with secondary amines and aldehydes/ketones represent a special case, as the prototypical Mumm rearrangement cannot take place. 2 …”
mentioning
confidence: 99%
“…Many noval MCRs [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] have meanwhile become part of the range of syntheses, e.g. boron-mediated [62,66], photo-induced [67] and carbenebased MCRs [72] such as N-heterocyclic carbenes (NHCs).…”
Section: Methodsmentioning
confidence: 99%
“…In summary,wehave developed anovel chiral phosphoric acid catalyzed enantioselective reaction between isonitriles (3)and 3-(arylamino)isobenzofuran-1(3H)-ones (7)toafford Angewandte 3-oxo-2-arylisoindoline-1-carboxamides (4)i nh igh yields with good to high enantioselectivities.Acatalytic enantioselective Ugi reaction of 2-formylbenzoic acids (1), anilines (2), and isonitriles (3)w as subsequently developed for the first time and lead to the same heterocycles 4.Mechanistic studies indicate that the observed enantioselectivity results from aDKR of the primary Ugi adduct rather than from the CÀC bond-forming process.W hile ag reat number of DKRs have been developed dealing with specific substrates, [25] DKR of ar eaction intermediate as am eans to achieving enantioselectivity remains an underexploited field. [26] Acknowledgments Financial supports from National Natural Science Foundation of China (21320102002, 21502202) and the EPFL (Switzerland) are gratefully acknowledged.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…Indeed, its presence renders the development of an enantioselective process extremely difficult since carboxylic acid is not only areactant, but also acatalyst for the classic Ugi reaction. We report herein an ovel CPA-catalyzed enantioselective reaction between isonitriles (3)a nd 3-(arylamino)isobenzofuran-1(3H)-ones (7), as well as the first examples of the Ugi fourcenter three-component reaction of 2-formylbenzoic acids (1), anilines (2), and isonitriles (3)f or the synthesis of enantioenriched 3-oxoisoindoline-1-carboxamides (4). [15] We also document that the observed enantioselectivity results from the dynamic kinetic resolution (DKR) of the primary Ugi adduct, rather than from the CÀCbond-forming step.The heterocycle 4 is known for its analgesic properties [16] and has [17] and medicinally relevant compounds,s uch as (R)-pazinaclone,asedative and anxiolytic drug.…”
mentioning
confidence: 99%
See 1 more Smart Citation